Observation of electromagnetic coupling to a closed superconducting thin-film cavity. - Thomas, C.D (IEEE Transactions on applied superconductivity)
We have studied Josephson junctions coupled to closed, superconducting, thin-film cavities. We briefly discuss the coupling mechanism in this system as well as the fabrication methods and expected resonant modes. Cavities consisting of both quartz and anodized niobium were studied. Small current steps have been observed in the current-voltage (I-V) measurements of junctions at voltages corresponding to the calculated modes of the closed cavity indicating Josephson coupling